(untitled) (American Journal of Pedagogical and Educational Research, 2026)
This article analyzes the development trends of the global education system and the science of pedagogy in the 20th–21st centuries. In particular, modern pedagogical approaches, models of education systems, and the significance of global educational projects in Western Europe, the USA, Russia, and CIS countries are highlighted. In addition, the ideas of reformist pedagogy and their impact on modern education are examined on a scientific basis.